ANALISIS PERUBAHAN TUTUPAN LAHAN DI TAMAN HUTAN RAYA GUNUNG TUMPA MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Christomus Bode; Fabiola B. Saroinsong; Johny S. Tasirin; Johan A. Rombang (COCOS, 2015)
ABSTRACK  This research presents land cover conversions on Mount Tumpa Forest Park within the 2007-2014 period; what was converted, where it happened, and how big those conversions were. The results shows that there are six classes of land cover, namely secondary forest, teak forest, buses, farm fields, mixed plantation, and coconut plantation. That there were a variety of conversions between classes in all observed villages : (1) secondary forest to coconut plantation, mixed plantation, bushes and fields (5.90%), (2) mixed plantation to bushes (0.23%), (3) coconut plantation to mixed plantation (0.61%), (4) fields to mixed plantation, bushes and secondary forest (4.74%). Even though some areas classified as bushes and farm fields were converted into secondary forests, the conversion of secondary forests to other classes (coconut plantation, mixed 2  plantation, bushes, and fields) is bigger in comparison, thus causing a decrease of the forest area by 1.03 ha.Or  175.13 to 174.10 ha between 2007-2014.   Keywords: Forest area decrease, land cover conversion, GIS